Risk factors for cervical chlamydial infection among women of reproductive age in an urban poor area in Manila - Nguyen Vu Thuong (2001)
To assess the association of cervical chlamydial infection (CCI) with early sexual debut (ESD), multiple partners (MP) and oral contraceptive use (OCU).This cross sectional study wa conducted in Dr. Jose Fabella Memorial Hospital (DJFMH) in Manila from October 1999 to June 2000. Five hundred women with vaginal discharge, aged 18 to 50 years, not pregnant and no vaginal bleeding were invited to participate in the study. Using a standard interview schedule, the study subjects were interviewed and physically examined by health care workers. Samples of vaginal and cervical specimens were also collected for laboratory diagnostics. Chlamydia trachomatis infection was diagnosed using polymerase chain reaction (PCR). Multivariate logistic regression analysis was used to assess the relationship between a suspected risk factor and CII while simultaneously adjusting for several socio-demographic, obstetric, gynecologic factors and sexual partner's characteristics.The prevalence of CCI among women with vaginal discharge, who consulted at DJFMH was 12.6(95CI: 9.9, 15.9). ESD (OR=2.8; 95CI: 1.14, 6.83; p=0.024) and MP within the last three months (OR=6.8; 95CI: 1.63, 28.5; p=0.009) were significantly associated with CCI. Among women whose spouses were drivers, those who used oral contraceptives for at least three months were nearly 22 times more likely to have CCI than women in the reference group. No significant assocaition between OCU and CCI was seen among women whose spouses were not drivers.Risky sexual behavior and possible biologic influences on the lower genital may account for an increased risk for CCI among females who had ESD. Some biologic changes among women whose spouses are drivers, especially when they use oral pills, may explain the interaction between 'driver-spouse' and OCU. Besides MP, OCU together with occupation of spouses (drivers) and ESD should be incorporated with other known risk factors in assessing women's risk to improve the diagnostic validity of the algorithm for cervicitis among women with vaginal discharge.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Cervical chlamydial infection